Love founded in God: The fruits of love in Kierkegaard’s ‘Works of love’ - Jos Huls (HTS Teologiese Studies/Theological Studies, 2011)
This article discussed the use of the Bible in ‘Love’s hidden life and its recognizability by its fruits’, which is the first reflection of Søren Kierkegaard’s book, Works of love. Firstly, this article discussed Kierkegaard’s lack of clarity about the fruits of love, even though he stresses their divine origin. Secondly, it reflected on his argument that, even though deeds are more important than words, words remain necessary because of the need to express love to others. In a following section he points out that neither specific words nor particular works of love can demonstrate that love exists. One needs to distinguish between works of love and the attitude with which works are done. Thirdly, it pointed out how Kierkegaard argues that the inability to demonstrate love unconditionally does not negate that love is to be known by its fruits. It is rather a personal incitement to love for the sake of love itself. Noting that there is no direct relationship between the fruits of love and the actual effects our love has on others, he points to the fact that the result of love is in the hands of God. He then argues that though fruits of love may be invisible, they become apparent in the strength of our love. The only responsibility we have is to follow love as the divine movement of our heart. In the final part of his reflection, Kierkegaard notes that there is no other way to enter into the reality of love than to believe in it. This implies that one should be careful of making demands on someone in a loving relationship. What is needed is to become rooted in love as the divine source of the heart so that one will understand that this unseen reality is the foundation of existence in which one is known by the Other, whose essence is love.